2020
DOI: 10.1021/acs.jproteome.0c00252
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive, Rapid, Robust, and Reproducible Workflow for Host Cell Protein Profiling in Biopharmaceutical Process Development

Abstract: There is a growing industry and regulatory need to detect host cell protein (HCP) impurities in the production of protein biopharmaceuticals, as certain HCPs can impact product stability, safety, and efficacy, even at low levels. In some cases, regulatory agencies require the identification and the quantification of HCPs in drug products (DPs) for risk assessment, and this is an active and growing topic of conversation in the industry and amongst regulators. In this study, we developed a sensitive, robust, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…We then compared our results to published HCP results for the NISTmAb that were determined using different digestion conditions, LC separation methods and MS systems (Figure 1a). 22,[26][27][28] As expected, the majority of HCP reported in other LC-MS analyses were identified in our experiment (Figure 1, Supplemental Table S1). In addition, 13 HCP identified in this study but not in the published studies were verified against much longer lists of NISTmAb HCP identified using more advanced HCP enrichment methods.…”
Section: Nistmab -Benchmarkingsupporting
confidence: 75%
“…We then compared our results to published HCP results for the NISTmAb that were determined using different digestion conditions, LC separation methods and MS systems (Figure 1a). 22,[26][27][28] As expected, the majority of HCP reported in other LC-MS analyses were identified in our experiment (Figure 1, Supplemental Table S1). In addition, 13 HCP identified in this study but not in the published studies were verified against much longer lists of NISTmAb HCP identified using more advanced HCP enrichment methods.…”
Section: Nistmab -Benchmarkingsupporting
confidence: 75%
“…(2021) [64] (yellow), Ma et al. (2020) [36] (purple), and in the current study (blue). All studies used a native digestion protocol adapted from Huang et al.…”
Section: Resultssupporting
confidence: 55%
“…[11] Lipoprotein lipase, in particular, can contribute to polysorbate degradation by hydrolysis. [3,62] Polysorbate degradation can lead to the formation of acetic acid, formic acid, reactive aldehyde/ketones, peroxides, and free fatty acids, which affects the stability and shelf life of the protein product. [10] The identification and assessment of these problematic impurities that cause product or surfactant degradation in the formulation can help improve the quality of a product.…”
Section: Formulationmentioning
confidence: 99%
“…[ 11 ] Lipoprotein lipase, in particular, can contribute to polysorbate degradation by hydrolysis. [ 3,62 ] Polysorbate degradation can lead to the formation of acetic acid, formic acid, reactive aldehyde/ketones, peroxides, and free fatty acids, which affects the stability and shelf life of the protein product. [ 10 ]…”
Section: Formulationmentioning
confidence: 99%